Interpreting Objects in the Hybrid Museum Convergence, Collections and Cultural Policy, 1st edition - Robinson, Helena (Routledge, 2020)
Interpreting Objects in the Hybrid Museum examines the recent trend for converged collecting institutions and uses its investigation as a catalyst for critical reflection by all stakeholders on the risks, as well as advantages, of integration for cultural engagement.